Big Nate : blasts off - Peirce, Lincoln (New York : Balzar + Bray, 2016)
After his fight with Randy Betancourt makes headlines in the school paper, Big Nate has a problem worse than detention on his hands.
3.3
3-6
GN460L
Keywords: Human behavior -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Behavior -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Human behavior -- Fiction; Friendship -- Fiction; School stories; Humorous stories; Graphic novels; Humorous fiction